Editorial [Hot topic: Antimicrobial Plant Peptides Isolated from Native and Crop Species in Brazil: Development of New Drugs (Guest Editor: Sergio Crovella)] - Crovella, Sergio (Current Protein and Peptide Science, 2010)
The central idea of this issue is to describe and discuss the potentialities of antimicrobial molecules isolated from native plant species of Brazil known to be employed by Amerindian populations as powerful antimicrobial drugs used in the traditional popular medicine, and from plants with great commercial and social interest such as sugarcane and legumes, respectively used for sugar as well as biofuels production and basic daily people feed. The enormous biodiversity of these plants represents a very powerful target to new drugs searching. The objective is to describe the progresses on seeking for new molecules with potential antimicrobial activity and new antimicrobial peptides able to fight against pathogen infections. The different topics of this issue describe the genomic and post-genomic strategies used to isolate new genes encoding for antimicrobial peptides, the in silico search for new antimicrobial molecules, the strategies for protein data mining in public databases and the suitable technologies for plant-derived antimicrobial peptides synthesis. The extraordinary biodiversity of native plants in Brazil, known to be used as alternative medicine approach by native Amerindian populations, is described in the Ethnobotanic topic, while epidemiological and pharmacological studies evidence several plant species as potential candidates for the development of new alternative drugs which are supposed to protect mucosal surfaces from microbes entrance and establishment. The approach described for identification of new interesting antimicrobial molecules relies on searching in silico the genes putatively coding for potential antimicrobial molecules already reported in public or in some private (such as SuperSAGE libraries from tolerant cultivated genotypes after pathogen infection) plant databases. The availability of such data shall substantially enhance understanding of genes and enzymes associated with natural products biosynthesis. The isolation of these molecules from native plants (where they have never been isolated from), the synthesis of these molecules and finally the in vitro testing for the potential antimicrobial activity will provide the researchers with better tools to fight against pathogens. Moreover, attention is focused on plants harboring social and economical relevance such as the sugarcane and members of the legume family. In fact sugarcane represents a central point in Brazilian northeastern economy since it is used to produce mainly the alternative biofuel ethanol and sugar, while the legumes are important part of the widely used popular food. The isolation of new antimicrobial peptides from these plants will allow the improvement of strategies for struggle against parasites and could reduce the negative effects of pesticides on the agricultural workers and the environment. The great efforts of the scientific community for the discovery of new drugs or nutraceuticals are nowadays directioned to the search of “natural” molecules, sometimes already known by ancient or traditional popular medicine or agriculture as efficient antimicrobials. The joint efforts including ethnobotanic, molecular biology and evolutionary genetics, biochemistry and cellular biology as well as epidemiology and bioinformatics are turning available the identification of a growing number of antimicrobial molecules with interesting potential applications; in this issue we discuss the different research strategies aiming the identification of antimicrobial molecules derived from native and crop Brazilian plant species and the potentiality of the results obtained so far.